2020
DOI: 10.31362/patd.669733
|View full text |Cite
|
Sign up to set email alerts
|

Sağlık çalışanlarının şiddet algısı, şiddete uğrama ve şiddetten etkilenme durumları Sağlık çalışanlarında şiddet

Abstract: Özet Amaç: Şiddet toplumun genelinde olduğu gibi sağlık çalışanları için de önemli bir sorundur. Bu çalışmada sağlık çalışanlarının şiddet algısının, şiddete maruz kalma sıklıklarının ve şiddetten etkilenme durumlarının değerlendirilmesi amaçlanmıştır. Gereç ve yöntem: Denizli ili merkez sağlık kuruluşlarında görev yapan ve çalışmaya katılmayı kabul eden 965 kişi çalışmaya dahil edilmiştir. Araştırmacılar tarafından literatüre dayanarak oluşturulan anket ile şiddetin tanımı, şiddetin olası nedenleri, şiddetin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…There are many studies carried out in Turkey in which violence against healthcare workers varies by the department (99.7% for 112 employees, 90.4% for emergency service workers, 43.4% for paediatric service workers, 73.8% for inpatient services, 65% for primary care workers, etc. ), the type of violence that is exerted (physical violence at varying rates, such as 9.6% 16.7%, 20% and 23.2%; verbal violence at varying rates, such as 78.3%, 82%, 95.7% and 99.7%) and the profession (85% towards nurses, 69.4% towards research assistant doctors and 54.5% towards specialists) (Akbaş et al, 2016;Cerit et al, 2018;Coşkun & Karahan, 2019;Çuvadar & Ekuklu, 2020;Demirci & Uğurluoğlu, 2020;Oğuz et al, 2020;Şahin & Yıldırım, 2020;Yücens & Oğuzhanoğlu, 2020). It has been reported that nurses, who are in close contact with patients and patient relatives while giving care, are exposed to violence by patients and patient relatives due to factors, such as long waiting times in health institutions, an inadequate number of healthcare workers, lack of security personnel, lack of information about the responsibilities of healthcare professionals by patients and their relatives, poor working conditions, lack of professional experience, and working in the night shift (Angland et al, 2014;Fallahi Khoshknab et al, 2015;Park et al, 2015).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…There are many studies carried out in Turkey in which violence against healthcare workers varies by the department (99.7% for 112 employees, 90.4% for emergency service workers, 43.4% for paediatric service workers, 73.8% for inpatient services, 65% for primary care workers, etc. ), the type of violence that is exerted (physical violence at varying rates, such as 9.6% 16.7%, 20% and 23.2%; verbal violence at varying rates, such as 78.3%, 82%, 95.7% and 99.7%) and the profession (85% towards nurses, 69.4% towards research assistant doctors and 54.5% towards specialists) (Akbaş et al, 2016;Cerit et al, 2018;Coşkun & Karahan, 2019;Çuvadar & Ekuklu, 2020;Demirci & Uğurluoğlu, 2020;Oğuz et al, 2020;Şahin & Yıldırım, 2020;Yücens & Oğuzhanoğlu, 2020). It has been reported that nurses, who are in close contact with patients and patient relatives while giving care, are exposed to violence by patients and patient relatives due to factors, such as long waiting times in health institutions, an inadequate number of healthcare workers, lack of security personnel, lack of information about the responsibilities of healthcare professionals by patients and their relatives, poor working conditions, lack of professional experience, and working in the night shift (Angland et al, 2014;Fallahi Khoshknab et al, 2015;Park et al, 2015).…”
Section: Backg Rou N Dmentioning
confidence: 99%